EFEKTIVITAS MEDIA AUDIO VISUAL DALAM MENINGKATKAN KEMAMPUAN MENYIMAK PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS III SEKOLAH DASAR - G.S.E. Handrayani (Universitas Trilogi, 2021)
This research is motivated by the low listening ability of students in learning Indonesian. This study. aims to improve the listening ability of Class III students at SDN Klender 03 Pagi through the application of audio-visual media. The subjects of this research were 28 students of Class III SDN Klender 03 Pagi. Data collection techniques used are tests, observations, interviews, field notes, and documentation. This research was conducted in 3 cycles with 3 actions in each cycle. The results showed that audio-visual media can improve students' listening skills. This is indicated by an increase in the average value before giving the action to cycle III. The average value obtained in the first cycle reached 57.31, in the second cycle the average value obtained increased to 75.36, and in the third cycle, the average value obtained increased to 88.89. In general, it can be concluded that the application of audio-visual media can improve students' listening skills in Indonesian lessons in Class III Elementary School.